Effects of ocean acidification on growth and physiology of Ulva lactuca (Chlorophyta) in a rockpool‐scenario. Issue 3 (29th April 2013) - Olischläger, Mark; Bartsch, Inka; Gutow, Lars; Wiencke, Christian
Summary Rising atmospheric CO2‐concentrations will have severe consequences for a variety of biological processes. We investigated the responses of the green alga Ulva lactuca (Linnaeus) to rising CO2‐concentrations in a rockpool scenario. U. lactuca was cultured under aeration with air containing either preindustrial pCO2 (280 μatm) or the pCO2 predicted by the end of the 21st century (700 μatm) for 31 days. We addressed the following question: Will elevated CO2‐concentrations affect photosynthesis (net photosynthesis, maximum relative electron transport rate (rETR(max)), maximum quantum yield (Fv/Fm), pigment composition) and growth of U. lactuca in rockpools with limited water exchange? Two phases of the experiment were distinguished: In the initial phase (day 1–4) the Seawater Carbonate System (SWCS) of the culture medium could be adjusted to the selected atmospheric pCO2 condition by continuous aeration with target pCO2 values. In the second phase (day 4–31) the SWCS was largely determined by the metabolism of the growing U. lactuca biomass. In the initial phase, Fv/Fm and rETR(max) were only slightly elevated at high CO2‐concentrations, whereas growth was significantly enhanced. After 31 days the Chl a content of the thalli was significantly lower under future conditions and the photosynthesis of thalli grown under preindustrial conditions was not dependent on external carbonic anhydrase. Biomass increased significantly at high CO2‐concentrations. At low CO2‐concentrations most adult thalli disintegrated between day 14 and 21, whereas at high CO2‐concentrations most thalli remained integer until day 31. Thallus disintegration at low CO2‐concentrations was mirrored by a drastic decline in seawater dissolved inorganic carbon and HCO3−. Accordingly, the SWCS differed significantly between the treatments. Our results indicated a slight enhancement of photosynthetic performance and significantly elevated growth of U. lactuca at future CO2‐concentrations. The accelerated thallus disintegration at high CO2‐concentrations under conditions of limited water exchange indicates additional CO2 effects on the life cycle of U. lactuca when living in rockpools.